The Implementation of ‘Aqīqah in Cultural Societies From a Hadith Perspective - Hemawati, Hemawati; Arbeni, Wawan; Dahlan, Zaini; Patra, Naziha (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to examine the implementation of ‘aqīqah in the multicultural community of Binjai City from the perspective of hadith, as well as to develop contextual hadith-based educational guides. This research uses a qualitative approach with a type of ethnography. The main data in the form of the practice of implementing ‘aqīqah is reviewed from the hadith. The data sources include religious leaders, educational leaders, and the community implementing ‘aqīqah who were selected purposively in five sub-districts of Binjai City. Data collection techniques are carried out through direct observation of ‘aqīqah activities, semi-structured interviews to explore the understanding of hadith, and documentation in the form of event archives, photos, and lecture scripts. Data analysis is carried out through three stages, namely data reduction to sort out relevant information, presentation of data in the form of thematic narratives, and inductive conclusion drawing to see the relationship between the understanding of hadith and the socio-religious practices of the community. The results of the study show that although the community understands ‘aqīqah as part of the teachings of the Prophet PBUH, the practice is greatly influenced by local culture and economic factors. Many processions are adapted, even mixed with non-sharia traditions. The conclusion of this study emphasizes the importance of adaptive hadith-based education and the preparation of guidelines for the implementation of ‘aqīqah in accordance with the context of modern society.